BIM 데이터 기반 현장 시공관리 사례 분석 연구 - 이동준; 현진오; 민성규; 임지용; 신민철; 권석현; Lee, Dong-Jun; Hyun, Jin-Oh; Min, Sung Gyu; Lim, Ji-Yong; Shin, Min Cheol; Kwon, Suk Hyun (KSCE Journal of Civil and Environmental Engineering Research, 2024)
The Ministry of Land, Infrastructure and Transport presented the "Construction Industry BIM Enforcement Guidelines Constructors Edition" to reflect the design BIM data in the construction stage. The enforcement guidelines were prepared with the aim of providing guidelines for detailed common implementation plans such as minimum BIM business methods and procedures necessary for ordering, designing, and construction stages for the full-scale BIM application in all fields of the construction industry. In this study, interference and design errors were examined based on the enforcement guidelines, and the application effects were grasped for various sites where equipment placement and operation plans were established. As a result, intuitive examination was possible by comparing the digital field 3D model and the planned model in one space, and the optimum equipment arrangement and operation plan were derived through simulation examination according to the execution stage. 국토교통부에서는 설계 BIM 데이터를 시공 단계에 반영하기 위해 『건설산업 BIM 시행지침 시공자 편』을 제시하였다.(이하, '시행지침'이라 함.) 시행지침은 건설산업 전 분야의 전면 BIM 적용을 위하여 발주, 설계, 시공단계에 필요한 최소한의 BIM 업무 방법 및 절차 등의 세부 공통 실행방안의 가이드라인을 제공하기 위한 목적으로 작성되었다. 본 연구에서는 시행지침을 기준으로 간섭 및 설계오류를 검토하고, 장비배치 및 운영계획을 수립했던 다양한 현장에 대해 적용 효과를 파악하였다. 그 결과, 디지털 현장 3D 모델과 계획 모델을 한 공간에서 비교하여 직관적인 검토가 가능하였고, 시공 단계별 시뮬레이션 검토를 통해 최적의 장비배치 및 운용계획을 도출하였다.